Prediction Model of Battery State of Charge and Control Parameter Optimization for Electric Vehicle - Wahono, Bambang; Ismail, Kristian; Ogai, Harutoshi (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2015)
This paper presents the construction of a battery state of charge (SOC) prediction model and the optimization method of the said model to appropriately control the number of parameters in compliance with the SOC as the battery output objectives. Research Centre for Electrical Power and Mechatronics, Indonesian Institute of Sciences has tested its electric vehicle research prototype on the road, monitoring its voltage, current, temperature, time, vehicle velocity, motor speed, and SOC during the operation. Using this experimental data, the prediction model of battery SOC was built. Stepwise method considering multicollinearity was able to efficiently develops the battery prediction model that describes the multiple control parameters in relation to the characteristic values such as SOC. It was demonstrated that particle swarm optimization (PSO) succesfully and efficiently calculated optimal control parameters to optimize evaluation item such as SOC based on the model.